The Ideas of Progressivism in American Impressionism - Vašina, Matěj (Univerzita Pardubice, 2024)
This bachelor thesis deals with the analysis of American Impressionism in the context of Progressivism. The theoretical part defines Progressivism with its historical, cultural, and social context (Gilded Age, women's suffrage, and racial issues) in the late 19th and early 20th century, along with its ideologies. It also characterises Impressionism and its various forms in the American context (Pennsylvania, California, and Ashcan School), together with an introduction to American Impressionists. The practical part thoroughly analyses paintings of individual American Impressionists (Childe Hassam, Mary Cassatt, John S. Sargent, William M. Chase, John H. Twachtman, and Theodore Robinson) and compares American and French Impressionism. The aim of this thesis is to answer the question of whether or not American Impressionism can be seen as a part of the Progressivism movement and, subsequently, how it differs from European Impressionism.
Myšlenky progresivismu v americkém impresionismu
Keywords: americký impresionismus; impresionismus; Hassam, Childe; Sargent, John S.; Cassatt, Mary; pozlacený věk; progresivismus; rasové problémy; umění; volební právo žen; american Impressionism; art; Gilded Age; Impressionism; progressivism; racial issues; women's suffrage